Soil ameliorant gypsum can improve pod yield of groundnut (Arachis hypogaea) - Kadirimangalam, Sai Rekha; Sawargaonkar, Gajanan; Choudhary, Pushpajeet (Indian Farming, 2024)
Gypsum was initially introduced as heavily subsidized ameliorant for treating alkaline soils in India. Over a period of time, gypsum being a cheap source of calcium and sulphur, farmers began to use it as a fertiliser in oilseeds production. Moderate solubility of gypsum helps in the ready availability of both the nutrients (calcium and sulphur) syncing with the critical growth stages of the plant. Many research trials proved that in groundnut, application of gypsum during the flowering stage enhances pod filling eventually increasing the pod yield along with improved seed quality. The application of right dose of gypsum at the right time not only improves the productivity but also minimizes environmental pollution. This study provides an overview of gypsum’s role in the improvement of pod yield, its advantages and absorption of gypsum by roots and pods from the soil in groundnut crop.